Conflicts Of Moral Values In Nathaniel Hawthorne's Young Goodman Brown - Widayuni, Rustiti (2012)
The objectives of the research are 1) to describe how Goodman Brown's anxiety is reflected in the fiction, 2) to describe the factors cause Goodman Brown's anxiety, and 3) to describe how he responds to his anxiety. Related to the above problem, the writer thought that the main character's anxiety is caused by internal factor and external factor. Internal factor is the factor coming from the character's psychological condition, and the external factor in the factor outside the character. The research methods include the subject of the study, that is the fiction Young Goodman Brown written by Nathaniel Hawthorne in 1983. In conducting the research, the writer uses a descriptive study, particularly library study. In this thesis, the standard criteria deal with the characteristics of anxiety namely; (1) repression, (2) projection, (3) denial, (4) avoidance, and (5) somatization. By means of the characteristics, the writer of this thesis is going to analyze and interpret the fiction Young Goodman Brown. The data of the study are primary data and secondary data. In order to analyze the fiction, the researcher uses psychological, sociological and structural approaches. The researcher analyzes anxiety of the main character through extrinsic and intrinsic aspects of the fiction. The results of the research showed that Goodman Brown's anxiety is reflected through five stages that are general anxiety, anxiety disorder, stress, phobia, and hysteria. The anxiety is caused by two general factors, internal factor and external factor. The internal factor causing Goodman Brown's anxiety comes from Goodman Brown's himself. From the beginning, he already has weak faith about his religion. He always feel doubtful whether Puritan teaching is true or false. So he decides to do traveling. Unfortunately, the travel in fact, ruins his faith. The external factor is the contribution of other elements causing Goodman Brown's anxiety. Goodman Brown's meeting with Old man, Goody Cloyse, Deacon Goakin, The Minister and Faith makes Goodman Brown's anxiety getting worse. Goodman Brown responses his anxiety through repression or forgetting, avoidance, denial, and somatization. When he leaves Faith to do traveling, he feels anxious of leaving Faith. But he responses his anxiety through forgetting. As he meets the Old man, he sees many respectable men joining the evil meeting, his anxiety is getting worse. He doesn't believe the fact and makes avoidance. Then, he makes avoidance by refusing his fellow-traveler to continue his journey into ix the deep forest. After he knows that Faith also joins the meeting, Goodman Brown experiences somatization. His heart becomes beating hard and hysteric Related to the research findings above, the writer wanted to propose some suggestions. The structural approach is very important for the students of literature to master because it is the primary approach. They can analyze any literary works such as: novels, short stories, and dramas. What they analyze is the text by making careful analysis of the plot, the characters, the setting, the tone, the theme, and so on. Hence, they can make further analysis of the literary works on the basis of structural approach. The story Young Goodman Brown which analyzed by the writer may a good source of information for the other researcher who are interested in it and want to make the same and different analysis. As we know, there are many approaches in analyzing literary works. The writer suggests that the next researcher will make analysis of Young Goodman Brown with other approaches.